Loss of rice after ripening by mechanical harvest in Heilongjiang Province - Sun, Hongyan; Gu, Yingnan; Zhang, Yu; Zhang, Haifeng; Guan, Xianren; Wang, Jingyuan (Frontiers in Sustainable Food Systems, 2025)
Heilongjiang Province is a major production base of commercial grain in China. Its rice output accounts for about half of the national total. During the rice harvesting stage carbon emissions account for approximately 15–20% of the entire rice planting process. This makes it necessary to enhance the efficiency of mechanical operations, reduce diesel consumption, lower carbon emissions, minimize the loss of rice yield at the same time, and to improve the mechanical harvesting effect of rice. Chinese scholars have conducted extensive researches on post-harvest grain loss reduction, mainly focusing on the safe storage of grain by farmers. Few scholars have conducted researches on rice harvesting and the yield loss after harvesting. Meanwhile, foreign scholars mostly considered the details from the perspective of producers’ behavior and the precision of the rice harvester. In Heilongjiang Province rice is mainly harvested by combine harvester, and the inappropriate harvest timing and excessive machine speed of harvest are easy to cause rice loss. Therefore, based on the reality of the main rice varieties, planting patterns and field management methods currently in the main production areas, this study conducts experiments on the rice loss during the rice harvesting stage for different influencing factors such as rice harvester models, harvester traveling speed, harvesting time, rice humidity, stubble height and storage methods. Then single factor ANOVA and correlation analysis are used in this article, using Duncan test method for multiple comparison and difference significance analysis. The results show that a relatively later harvest time, a rice moisture content of 20–22%, a lower traveling speed of the harvester (5–6 km/h), and an appropriate stubble height (14–18 cm) can effectively reduce the amount of rice grain shedding about 1–1.5%. In this study, the main focus was on examining the effects of moisture content during rice harvesting, the speed of the harvesting machine, and the height of stubble left on the field on the loss of rice. Apart from the aforementioned factors that will significantly affect the post-harvest loss level of rice, human factors will also have relevant impacts on it. But this will be carried out in the next stage of the research.